Circle Gardening : Growing Vegetables outside the Box - Spaeth, Kenneth E., Jr (Book collections on Project MUSE., 2018)
As more people become concerned with food safety as well as the environment, vegetable gardening offers an opportunity to grow produce at home. Not everyone has the time, money, or energy to take on the challenge of starting a vegetable garden, however. In Circle Gardening, Kenneth E. Spaeth Jr., a soil and ecosystem specialist, provides a fresh approach and thorough guide to vegetable gardening for all gardeners, experienced and beginner alike. Through years of experimentation, Spaeth has found circle gardening, an ancient method as old as agriculture, to be not only an efficient but also an aesthetically pleasing way to grow plants. By arranging them in a concentrated circle rather than in rows, gardeners are able to conserve compost, fertilizer, and water. Depending on the number of vegetables planted, this design can save time and be less physically demanding. The rationale for planting your veggies in a circle is scientific, too--many plants clump together in nature and thrive in groups, and so planting in circles actually mimics natural plant distribution. There are other questions that befuddle expert and beginner gardeners, too: What is the difference between organic and conventional gardening? Are there significant pros and cons to each? What makes up the soil in a garden? Spaeth provides clear answers to these complex questions. The book also includes quick vegetable guides in the back along with information on composting, calculating fertilizer rates, and gauging soil health.